Preparação e caracterização do compósito poli (fluoreto de vinilideno) / polianilina com partículas de níquel - Dias, Gabriel da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Conductors composites associate at conductors polymers with electrical and magnetic properties and metal particles with mechanical properties and processability of polymers conventional due the versatility and potential for technological applications, have been emphasized to researchers. In this work, composite PVDF/Pani/Ni magnetic properties were obtained by physical mixing the nickel particles and power resulting from synthesis of blend PVDF/Pani. Homogeneous films were obtained by hot pressing at a temperature 180°C and pressure 30 MPa. The thermogravimetric analysis of composites showed that they presented a good thermal stability with little weight lost to 300°C. The analysis scanning electron microscope with energy dispersive X-ray analysis confirmed the presence to Nickel particles in the end product and with the analysis by differential scanning calorimetry showed that the presence thereof did not change the conformational and configuration structure the polymer matrix preserving the characteristic peaks of α phase PVDF. The electrical conductivity PVDF/Ni composites and PVDF/Pani/Ni undoped, to the content of nickel particles showed percolation threshold between 15 and 20% with a range 7 and 5 orders of magnitude, respectively, reaching values near to nickel particles (10-4 S/cm). For redoped composite increasing content particles caused a decrease in the magnitude electrical conductivity 10-3 to 10-4 S/cm. The stress-strain tests showed that the presence of particles causes impoverishment in the mechanical properties to composite with decreasing resistance to deformation and rupture, as the conductor with insulating state. The magnetic analysis showed that the materials before pure changed to diamagnetic behavior and with the incorporation of particles are showed a ferromagnetic behavior. Analyses of reflectivity/absorption electromagnetic showed an increase of potency absorbed and reflected with increasing conductive ...

Compósitos condutores associando as propriedades elétricas e magnéticas de polímeros condutores e partículas metálicas com as propriedades mecânicas e processabilidade de polímeros convencionais, devido a versatilidade e potencial de aplicações tecnológicas, têm sido cada vez mais enfatizadas na área da pesquisa. Neste trabalho foram obtidos compósitos de PVDF/Pani/Ni com propriedades magnéticas, pela mistura física das partículas de Níquel e do pó resultante da síntese da blenda de PVDF/Pani. Filmes homogêneos foram obtidos por prensagem à quente a uma temperatura de 180°C e 30 MPa. As análises termogravimétricas dos compósitos mostraram que eles apresentaram uma boa estabilidade térmica com pouca perda de massa até 300°C. As análises de microscopia eletrônica de varredura acoplado à análise dispersiva de raios X confirmaram a presença de partículas de Níquel no produto final e juntamente com as análises de calorimetria diferencial de varredura mostraram que a presença das mesmas não alteraram a estrutura conformacional e configuracional da matriz polimérica preservando os picos característico da fase α do PVDF. A condutividade elétrica do PVDF/Ni e dos compósitos de PVDF/Pani/Ni desdopado, em função do conteúdo de partículas de Níquel apresentaram limiar de percolação entre 15 e 20% com um salto de 7 e 5 ordens de grandeza, respectivamente, alcançando valores próximos ao das partículas de Níquel (10-4 S/cm). Para o compósito redopado o aumento do conteúdo de partículas causou o decréscimo de uma ordem de grandeza na condutividade elétrica de 10-3 para 10-4 S/cm. Os ensaios de tração mostraram que a presença de partículas causa um empobrecimento nas propriedades mecânicas do compósito com a diminuição da resistência a ruptura e deformação, tanto para o estado isolante como condutor. O levantamento magnético mostrou que o material antes puro passa de um comportamento ...
Keywords: Polimeros; Polimeros condutores; Compositos polimericos; Niquel; Magnetismo; Polimeros - Propriedades eletricas; Polymers